Komposisi Isotop Stabil dan Trofik Level Kerang Kipas (Pectenidae: Chlamydinae sp.) dan Produsen Primer di Pulau Pari, Kepulauan Seribu, DKI Jakarta - Mardiansyah Mardiansyah; Yusli Wardiatno; Tri Prartono (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2013)
Scallop (Pectenidae: Chlamydinae sp.) is fauna habitat in seashore ecosystem and had commercial value commudity. The aims this study were to identify the main composition of stable isotopes, food sources, and trophic level from scallop and potential food sources to comparing isotopic signatures of different primary producers and fauna, and to estimate qualitatively the importance of material in ecosystem seashore. The researched conducted in Pari islands, Seribu Islands, DKI Jakarta, we analyzed the stable isotopes δ13C and δ15N. The composition signature of stable isotopes (δ13C and δ15N) scallop, seagrasses, macroalgae, and sponge showed significant differents (ANOVA; p < 0.05). Fractionation signature δ13C scallop with potential food sources is had not range. In addition, signature δ13C from scallop is not assimilated seagrass, macrolagae, and sponge. The signature δ15N from species, scallop had value riched than seagrass, macroalgae, and spong. The function scallop in trophic level had consumer and seagrass, macrolagae, and sponge is primary producer. Stable isotopes composition scallop is first study conducted in habitat Seribu islands.